Engaging the Digital Native Generation in Cultural Digital Preservation: Strategies and Approaches for Libraries and Librarians in the Digital Age 4.0 - Purnomo, Gabriel Wahyu; Pratiwi, Kurniasih Yuni (Brawijaya University Library, 2023)
Digital cultural preservation is becoming increasingly important in the digital 4.0 era, where the digital native generation has a central role in the use of digital technology. Libraries and librarians as custodians of knowledge and culture must engage the digital native generation in cultural digital preservation efforts. However, effective strategies and approaches need to be developed to ensure their active participation in this preservation. This study takes a qualitative approach to data collection, including in-depth interviews and a literature review. Data analysis was conducted using thematic techniques to identify strategies and approaches used in engaging the digital native generation. This study found that, several strategies and approaches were found to be effective in engaging the digital native generation in cultural digital preservation. Firstly, libraries should provide easy and intuitive access to cultural digital resources for the digital native generation. Second, a collaborative and participatory approach involves them in the process of curating and determining the direction of cultural digital preservation. Third, training and educational programs should be organized to improve digital literacy and understanding of the importance of digital cultural preservation. This study concluded that engaging digital native in digital cultural preservation requires a holistic and multifaceted approach. Libraries and librarians need to adopt strategies that are responsive to the needs and preferences of digital native. In the digital era 4.0, digital cultural preservation is not just a task for libraries, but a shared responsibility to ensure the sustainability and accessibility of digital cultural heritage for current and future generations.